Challenges for the UK pension system: The case for a pensions review - Jonathan Cribb; Carl Emmerson; Paul Johnson; Heidi Karjalainen; Laurence O'Brien (Institute for Fiscal Studies (IFS), 2023)
This report makes the case for a new review of the pension system in the UK. There are a number of key challenges facing future generations of pensioners that threaten their living standards in retirement and which, without policy action, mean many are likely to face substantial financial difficulties in older age. This is the first report of a multi-year project that will produce the highest-quality evidence regarding the future of financial security in retirement. The launch of our final report, which will include specific policy recommendations and options, is planned for early Summer 2025.
Keywords: 330; Employment and income; Savings; pensions and wealth; Taxes and benefits; The pensions review; Ageing; Benefits; Employment; Government spending; Housing; Inequality; Labour supply and workforce; Living standards; Pensioner benefits; Poverty; Private pensions; Public finance; Retirement; Savings